Pengaruh Sistem Rekrutmen dan Seleksi Terhadap Kinerja Karyawan Pada PT. Bank Sulselbar Palopo - Sri Febrianti; Saharuddin Saharuddin; Dirham Dirham (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2026)
This research aims to analyze the influence of the recruitment and selection system on employee performance at PT Bank Sulselbar Palopo, as well as the interaction between the two in influencing employee productivity. Using a quantitative approach and multiple linear regression analysis techniques, this research involved 50 employees as samples, taken using census sampling techniques. The research results show that the recruitment system has a positive and significant effect on employee performance, while selection has no effect and is not significant on employee performance. The results of the F test show that there is a significant interaction between Recruitment and Selection in influencing employee performance. The calculated F-value of 43.655 is greater than the F-table of 3.20 and the p-value of 0.001 is smaller than 0.05, indicating that these two variables together make a significant contribution to employee performance. This means that the combination of effective recruitment and good selection can create a greater impact on employee performance.